KOMPARASI PENDAPATAN USAHATANI UBI KAYU BERDASARKAN SALURAN PEMASARAN DI KECAMATAN TULANG BAWANG TENGAH, KABUPATEN TULANG BAWANG BARAT, INDONESIA - Lidya Sari Mas Indah; Wan Abbas Zakaria; Amanda Putra Seta; Gagah Wicaksono (Lampung University, 2026)
This research aims to analyze income farming and comparing the actual condition with the condition that should be in income farming of cassava in Tulang Bawang Tengah district, Tulang Bawang Barat regency. This research uses a survey method. This research was intentionally (purposive) in Tulang Bawang Tengah district with the consideration that the location was cassava production center in Tulang Bawang Barat Regency and has a tapioca factory as market location. Farmer petanits were chosen randomly. The results showed, there are two cassava marketing channels in Tulang Bawang Barat Regency, namely Channel I (Farmer–Factory) and Channel II (Farmer–Collector–Factory). The majority of farmers (90%) preferred Channel I because it is more efficient and generates higher profits than Channel II, which is used by only 10% of farmers. Cassava farming was profitable under both marketing channels, as indicated by R/C ratio values greater than one. However, Channel I generated higher farm income, amounting to IDR 6,053,909.81 per hectare based on cash costs and IDR 4,202,364.95 per hectare based on total costs, compared with Channel II, which generated only IDR 3,346,204.80 per hectare and IDR 776,610.51 per hectare, respectively. The R/C ratios of Channel I (1.68 and 1.39) were also higher than those of Channel II (1.48 and 1.11). These findings indicate that direct marketing to processing factories is more efficient and provides higher income for farmers than marketing through intermediaries. Keywords: cassava, income, marketing channel